Outcomes and Complications of Computed Tomography Guided Biopsy of Pulmonary Lesions; Our Experience - A Single Centre Experience (Medical Forum Monthly, 2023)
Objective: The purpose of this retrospective study is to share our experience, results and complications of CT-guided biopsy of lung lesions.Study Design: A retrospective cross-sectional studyPlace and Duration of Study: This study was conducted at the Interventional Radiology Department at Rehman Medical Institute Peshawar from February 2019 till December 2022.Materials and Methods: It was retrospectively analyzed. Patient demographics, lesion size and its depth, cores number, outcomes, positive biopsy rate, negative biopsy rate and complications are reviewed. All the data was analyzed by using SPSS version 24.Results: A total of 124 CT-guided pulmonary lesion biopsies were performed. 63 (50.81%) were female patients and 61 (49.19%) were male. The overall accuracy of CT-guided pulmonary lesions biopsies was 93.54 %, moreover, 4 (3.23%) cases were repeated for definite diagnosis, and 4 (3.23%) of them were inconclusive. 27 (21.77%) patients had post-biopsy complications which included minor hemoptysis (but the patients were stable and did not require any resuscitation) in 06 (4.8%) patients. Other complications like small pneumothorax were observed in 15 (12%), and 4 (3.2%) cases had pneumothorax which required aspiration with a 16-gauge cannula. Additionally, 2 (1.2%) of these patients collapsed after the biopsy and recovered after a cycle of CPR.Conclusion: CT-guided biopsy is a safe procedure to establish diagnosis of pulmonary lesions. Proper technique and tertiary care settings are required to manage post-biopsy complications.